Vibration response analysis and testing of a single-span bridge structure - Liau, Joshua Ming Xuan (Nanyang Technological University, 2021)
The study of vibration data has always been a keen point of interest for researchers. Vibration analysis involving the identification of modal parameters (mode shapes, natural frequencies, damping ratio etc.) has become prevalent over the years as well. Through vibration testing, followed by analysis of the data, the durability and reliability of structures or machinery could be determined. Abnormalities which are detected during analysis can also be monitored closely, potentially preventing any damage or disasters from occurring. The various means of testing include the Free Vibration Test, Forced Vibration Test, Ambient Vibration Test etc. In this report, it focuses exclusively on vibration testing of a single span footbridge located in North Spine, Nanyang Technological University (NTU). As it spans across North Spine to the National Institute of Education (NIE), with bus stops on both sides, it is classified as a bridge with high pedestrian volume. From the vibration response analysis, modal parameters of the bridge structure can be identified without direct access to its in-situ information, making it practical and cost-effective. Furthermore, the serviceability of the bridge would be explored, which encompasses factors like human comfort issues due to vibrations on the pedestrian bridge etc. Overall, the project scope covers the collection of vibration data via sensors, theoretical analysis of the data, computational analysis of the data via various software, and a summary of the overall work accomplished.